Social media and decision-making process among tourist: a systematic review - Noor Alyani Nor Azazi,; Maslina Mohammed Shaed, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social media nowadays have a huge influence on the tourism sector. With the advancement of search engines, tourists can search for any information they need on their tourism preferences. Today, there are tons of social media websites (such as TripAdvisor, Trivago, Booking.com, Agoda.com) that can help the tourist to find and decide the best tourism places and activities around the world. Studies have shown that social media is one of the best tools that are used by a tourist in the decision-making process. This paper is written to have a better understanding and to find a gap in the studies related to this topic. Hence, this paper focuses on conceptual review using a systematic review based on 24 published journals and theses from 2015 to 2019 on the influence of social media and its impact on the decision-making process for the tourist. Based on the findings, the majority of the scholars supported that social media have a big impact on how people make the decision for their tourism destination. The gaps that derived from this review have proven that only limited studies have been conducted in Malaysia; most of the research used a quantitative approach; only a few studies have included the theory related to this issue, and the targeted respondents were mostly among young travellers. Therefore, further studies on the role of social media in the decision-making process can be done by focusing on these gaps, especially in the Malaysian context.